Penyuluhan Kesehatan Tentang Pemberian Makanan Pendamping ASI (MP-ASI) Di Desa Buyut Udik Kecamatan Gunung Sugih Lampung Tengah - Primasari, Sefria Indah (CV. Tripe Konsultan, 2024)
High public health is a precondition for increasing human resource productivity. In relation to this, to create quality human resources, of course, many factors must be considered, including food factors (nutritional elements), health, education, information, technology and other service services. The purpose of Health Counseling on Providing Complementary Foods for Breast Milk is to update knowledge to mothers of babies and toddlers about Providing Complementary Foods for Breast Milk through Health Counseling. so that it can be used as a model for community empowerment in the form of efforts to increase active community participation. The method used in this activity is to provide Health Counseling on Providing Complementary Foods for Breast Milk. The result of this activity is that mothers understand the types and correct times to provide complementary foods for breast milk. The implementation of this Health Counseling has a positive impact on mothers of babies and toddlers in Buyut Udik, Central Lampung. After carrying out the counseling activity, knowledge about providing complementary foods for breast milk increased.